1996
DOI: 10.1016/0370-2693(95)01468-3
|View full text |Cite
|
Sign up to set email alerts
|

“Faster than light” photons and rotating black holes

Abstract: arXiv:gr-qc/9508048v1 22 Aug 1995 SWAT 95/71 Abstract The effective action for QED in curved spacetime includes equivalence principle violating interactions between the electromagnetic field and the spacetime curvature. These interactions admit the possibility of superluminal yet causal photon propagation in gravitational fields. In this paper, we extend our analysis of photon propagation in gravitational backgrounds to the Kerr spacetime describing a rotating black hole. The results support two general theore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
114
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(115 citation statements)
references
References 16 publications
0
114
1
Order By: Relevance
“…This concept has gained a central role in the discussion of the propagation of photons in non-linear electrodynamics. In particular, we stress that "anomalous" (c photon > c gravity ) photon speeds have been calculated in relation with the propagation of light in the Casimir vacuum [20][21][22], as well as in gravitational fields [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…This concept has gained a central role in the discussion of the propagation of photons in non-linear electrodynamics. In particular, we stress that "anomalous" (c photon > c gravity ) photon speeds have been calculated in relation with the propagation of light in the Casimir vacuum [20][21][22], as well as in gravitational fields [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that in general it is possible to find directions and polarisations for which the photon velocity exceeds the fundamental constant c. This work has subsequently been generalised to other examples of background spacetimes, including Reissner-Nordstrom and Kerr black holes [2,3]. In ref.…”
Section: Introductionmentioning
confidence: 88%
“…3 Just as in the QED case, the result can be stated as a curvature induced contribution to the refractive index for graviton propagation along the geodesic γ, 12) to O(G eff ). The result is actually simpler than the QED case in (1.3) since the result is diagonal in the 2-dimensional polarization space.…”
Section: The Gravitational Drummond-hathrell Effectmentioning
confidence: 99%